Telephone skills from A to Z - Friedman, Nancy J. (Crisp Pub. Menlo ParkUS, 1995)
Presents basic telephone courtesies, for example, being friendly before you know who it is; saying: please..., thank you..., you're welcome. Shows how to handle telephone conversation problems e.g. the slow/fast speaker, irate callers, foreign accents. Identifies behaviours to avoid in telephoning e.g. chewing gum, rushing callers. Lists 5 forbidden expressions - I don't know; just a second; no (at the beginning of a sentence); we can't do that; and, you'll have to...